Former Yugoslav Republic of Macedonia : Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report ;, 2018)
This report assesses the state of fiscal transparency practices in the Former Yugoslav Republic of Macedonia against the IMF's Fiscal Transparency Code. The report finds that Macedonia meets the standard of good or advanced practice on 13 of the 36 principles, and the basic standard on a further 12 principles. Moreover, in 5 of the areas where Macedonia's transparency practices do not currently meet basic practice, this could be addressed by publishing data that are already collected for internal management purposes. It is recommended to expand the institutional coverage of fiscal and statistical reports, to include the activities of all institutional units that would be classified as part of the general government under international statistical standards.